Developments in Mud Probing - Leenhardt, Olivier (The International Hydrographic Review, 2015)
The author first examines the physical conditions for mud probing measurements and then goes on to describe the instrumental possibilities. A transducer is characterized by its frequency, its mechanical Q, its directivity and its emission level. Among possible materials piezo-electric ceramics give the best results. The components of an instrument are briefly described, and then a short historical account of the method is given, showing how a decrease in working frequency and a reduction of the pulse length lead to better penetration and resolution. Several types of bottom are examined from the point of view of their interest in mud probing operations. Finally the conditions for operating these instruments both from the surface and from the bottom are studied, and possible future developments of the method are suggested, taking into account the users’ requirements as well as the most recent technical possibilities.